Dinamika dan Proyeksi Perubahan Tutupan Lahan serta Inkonsistensi Tata Ruang di Wilayah Pegunungan Kendeng - Andrea Emma Pravitasari; Ernan Rustiadi; Soeryo Adiwibowo; Imelda Kusuma Wardani; Iwan Kurniawan; Alfin Murtadho (P4W LPPM IPB, 2020)
Dynamics and Projections of Land Cover Changes and Spatial Plan Inconsistenciesin Kendeng Mountains Region Kendeng is limestone mountains that stretch across the northern part of Java Island. It is located in 7 regencies in 2 provinces (Pati, Grobogan, Blora, and Rembang Regenciy in Central Java Province; and Lamongan, Bojonegoro, and Tuban Regency in East Java Province). Kendeng Mountains is rich in natural resources and biodiversity. However, the development of mining activities and other cultivation activities has led to a dynamic land cover changes and threatens to damage the karst area of Kendeng Mountains. This research aims to: (1) identify the dynamics of land cover changes (LCC) in Kendeng Mountains (1996–2016); (2) conduct projections of the LCC in 2036; and (3) analyze spatial plan inconsistencies in the region. LCC analysis was conducted with ArcGIS 10.3 software using land cover maps of 1996, 2000, 2006, 2011, and 2016 from the Ministry of Environment and Forestry. Projections of LCC in 2036 was analyzed by CA-Markov using Idrisi Selva software. Spatial plan inconsistency analysis was carried out by overlaying land cover maps with Spatial Plan (RTRW) maps. Based on CA-Markov analysis, the mining area increased from 12 ha (1996) to 1,660 ha (2016), as well as built-up area from 83,543 ha (1996) to 96,761 ha (2016). The projection of land cover change predicts that mining area and built-up area in 2036 will increase to 3,646 ha and 110,843 ha. Existing area (in 2016) which is inconsistent with the Spatial Plan is 12.3%. Based on predicted LCC in 2036, it seems that the chances of spatial plan inconsistencies in this region will increase more in the future.